Developing Malay children's literary resources - Chew, F.P.; Arshad, M.; Ishak, Z.; Loh, S.C.; Teh, Y.W. (2009)
The materials and resources for Malay literature for early childhood in Malaysia are still in the infant stage and have not expanded to include main references or developed into big book form. The children literature in our market is not published based on education philosophy and research, but it is produced based on profit. The process of evaluating the quality of children's literature need to take into account the interest of the children, their visual ability, messages of the story, and the effect of the story towards the children. Hence a survey was carried out among 941 respondents including university students, preschool teachers and parents which were selected randomly in Malaysia. Learning outcomes identified the main features which attract the children to read. Malaysian children were found to be interested in stories with the themes of love, friendship and family, imaginative animals and funny characters, simple plots, colorful illustrations, big size story books with lot of dialog and video publications (DVDNCD). The main factors that are considered by parents when buying children's literature materials are the moral values, quality and activities in the stories. They are also requiring CALL activities such as ICT games and exercises to make teaching and learning more effective.